Preliminary studies in some aspects of carotenoid metabolism of tiger shrimp (Penaeus monodon fabricus) - Heralde, Francisco III M.
Studies on some aspects of carotenoid metabolism of black tiger shrimp (Penaeus monodon Fabricius) were conducted. The reactions of carotenoid metabolizing enzyme C-3 and C-4 monooxygenase were optimized. The Enzyme Activity Factor (EAF) was used which allowed identification of four possible reactions in the beta-carotene> astaxanthin pathways, namely: a) oxygenation b) reductive c) reductive-oxygenation and d) reductive cleavage. An extraction solvent containing 50 mM Tris-HCI buffer at pH 7.4 with 1.15% KCI and 1 mM EDTA was found optimal for the reactions. Hepatopancreas homogenates from live-starved shrimp samples exhibited oxygenation reaction with the former having thrice activity as the latter. Homogenate coming from fresh-chilled sample showed reductive-cleavage reaction. Oxygenation and reductive reactions occurred in incubation temperature range of 27-31C while reductive-cleavage reaction occured below 27C or above 31C. Incubation pH of 4-6 showed oxygenation reaction, while pH 7 and 8-10 showed reductive-oxygenation and reductive-cleavage respectively. The use of 14C-labelled astaxanthin and unlabelled beta-carotene to probe enzyme activity in various reaction mixtures demonstrated enzyme mediation inm both oxygenation and reductive reactions. Oxygenation reaction involving C-3 and C-4 monooxygenase was not found to require NADPH/NADH in contrast to reductive reaction. The presence of beta-carotene promoted oxygenation and reductive reactions. Studies on effects of hypoxia demonstrated carotenoid depleting effect mediated through enhanced fecal carotenoid release, promotion of reductive-cleavage reaction, elevated hepatopancreas carotenoid levels and increased hemolymph serum protein levels. Formation of beta-doradexanthin monoester possibly coming from astaxanthin monoester was detected. Subjection to three consecutive hypoxia challenges resulted to enhanced fecal carotenoid release and elevated hemolymph serum protein levels every after hypoxia challenge. Induction of BSX syndrome was achieved in 1-2 weeks, Posthypoxia, BSX positive shrimps contained lower total carotenoid content in different tissues like those of farmed blue shrimps. Carotenoid supplementation during hypoxia altered the carotenoid depleting effect of hypoxia. Beta-carotene supplementation (15 ppm.) caused temporary suppression of carotenoid fecal release which is reversed in succeeding hypoxia challenges as well as decreased reductive-cleavage activity of hepatopancreas enzymes. Astaxanthin supplementation (20 ppm) caused initial delays in fecal carotenoid release response up to two hypoxia challenges. Irregardless of carotenoid supplementation, meholymph serum protein levels remain elevated after hypoxia challenge. Carotenoid supplementation did not totally prevent BSX development in shrimps subjected to hypoxia challenge. Carotenoid supplementation in BSX-affected commercial ponds reduced BSX incidence with more apparent effect achieved with astaxanthin (45%) than beta-carotene (16%). Total carotenoid content of the different tissues were higher at post-supplementation while hemolymph serum protein levels were low. Total correction of BSX-incidence was not achieved in two weeks of carotenoid supplementation. The results obtained predicted the existence of an astaxanthin cool consisting of astaxanthin (A), astaxanthin monoester (AM), and astaxanthin diester (AD) which can be mobilized to different tissues and participate in various metabolic processed. As the physiological saturation point of the A-AM-AD pool is maintained, a slow carotenoprotein formation predisposes fecal clearance of carotenoids in excess of the saturation limit. The occurrence of BSX syndrome can be explained by the effect of hypoxia on the astaxanthin pool directly via conversion of astaxanthin monoester to betadoradexanthin monoester, and indirectly through involvement of energy and amino acid metabolism.
Theses--(Master in Science in Biochemistry) UPCM
Keywords: Carotenoids; Penaeus Monodon Fabricus